Correlation between the degree of leukoaraiosis and hyperlipidemia in post-ischemic stroke patients - Dian Angraeni; Lina Choridah; Evi Artsini (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Leukoaraiosis is a neurological imaging in the periventricular area and the centrum semiovale. This condition occurs due to abnormalities in the small blood vessels in the brain that lead to hypoxia. It is often observed in patients with ischemic stroke and accompanied by risk factors for hyperlipidemia. This study aimed to evaluate the correlation between the degree of leukoaraiosis and hyperlipidemia in post-ischemic stroke patients. A cross-sectional study retrospectively was conducted on post-ischemic stroke patients who underwent brain MRI (magnetic resonance imaging) on T2 and FLAIR (fluid-attenuated inversion recovery) sequence at the Department of Radiology, Dr. Sardjito General Hospital, Yogyakarta, from January 2021 to March 2022. A total of 36 patients were involved in this study. The leukoaraiosis of patient was examined by brain MRI. Degree of the leukoaraiosis was determined based on Fazekas classification. Serum cholesterol, HDL (high-density lipoprotein), LDL (low-density lipoprotein), and triglyceride levels of patients were then examined. The data obtained were then analyzed using Spearman correlation test. A positive correlation was observed between the degree of leukoaraiosis and triglyceride level (p = 0.042; r = 0.292) and age (p= 0.004; r = 0.464). However, no correlation was observed between the degree of leukoaraiosis and cholesterol, HDL, and LDL (p>0.05). In conclusion, the leukoaraiosis degree is correlated with serum triglyceride levels and age in post-ischemic stroke patients.